Multicenter, single-arm, phase II study (CAP) of radiotherapy plus liposomal irinotecan followed by camrelizumab and anti-angiogenic treatment in advanced solid tumors - Shen, Jie; Yan, Jing; Du, Juan; Li, Xiaoqin; Wei, Jia; Liu, Qin; Yong, Hongmei; Wang, Xiaolu; Chang, Xiaofeng; Ding, Zhou; Sun, Wu; Liu, Chenxi; et al. (Frontiers in Immunology, 2023)
Introduction Combination therapeutic mode is likely to be the key to enhance the efficacy of immunotherapy in a wider range of cancer patients. Herein, we conducted an open-label, single-arm, multicenter, phase II clinical trial that enrolled patients with advanced solid tumors who had progressed after standard treatments. Methods Radiotherapy of 24 Gy/3 fractions/3-10 days was given to the targeted lesions. Liposomal irinotecan (80mg/m2, dose could be adjusted to 60 mg/m2 for intolerable cases) was intravenously (IV) administered once within 48 hours after radiotherapy. Then, camrelizumab (200mg IV, q3w) and anti-angiogenic drugs were given regularly until disease progression. The primary endpoint was objective response rate (ORR) in the target lesions evaluated by investigators per RECIST 1.1. The secondary endpoints were disease control rate (DCR) and treatment-related adverse events (TRAEs). Results Between November 2020 and June 2022, 60 patients were enrolled. The median follow-up was 9.0 months (95% confidence interval (CI) 5.5-12.5). Of 52 evaluable patients, the overall ORR and DCR were 34.6% and 82.7%, respectively. Fifty patients with target lesions were evaluable, the ORR and DCR of the target lesions were 35.3% and 82.4%, respectively. The median progression-free survival was 5.3 months (95% CI 3.6, 6.2), and the median overall survival was not reached. TRAEs (all grades) occurred in 55 (91.7%) patients. The most common grade 3-4 TRAEs were lymphopenia (31.7%), anemia (10.0%), and leukopenia (10.0%). Conclusion The combination of radiotherapy, liposomal irinotecan, camrelizumab, and anti-angiogenesis therapy demonstrated promising anti-tumor activity and well tolerance in various advanced solid tumors. Clinical trial registration https://clinicaltrials.gov/ct2/home, identifier NCT04569916.